Pathogenic Relevance of IgG and IgM Antibodies against Desmoglein 3 in Blister Formation in Pemphigus Vulgaris - Tsunoda, Kazuyuki (American Society for Investigative Pathology, 2011)
Pemphigus vulgaris is an autoimmune disease caused by IgG antibodies against desmoglein 3 (Dsg3). Previously, we isolated a pathogenic mAb against Dsg3, AK23 IgG, which induces a pemphigus vulgaris-like phenotype characterized by blister formation. In the present study, we generated a transgenic mouse expressing AK23 IgM to examine B-cell tolerance and the pathogenic role of IgM. Autoreactive transgenic B cells were found in the spleen and lymph nodes, whereas anti-Dsg3 AK23 IgM was detected in the cardiovascular circulation. The transgenic mice did not develop an obvious pemphigus vulgaris phenotype, however, even though an excess of AK23 IgM was passively transferred to neonatal mice. Similarly, when hybridoma cells producing AK23 IgM were inoculated into adult mice, no blistering was observed. Immunoelectron microscopy revealed IgM binding at the edges of desmosomes or interdesmosomal cell membranes, but not in the desmosome core, where AK23 IgG binding has been frequently detected. Furthermore, in an in vitro dissociation assay using cultured keratinocytes, AK23 IgG and AK23 IgM F(ab′)(2) fragments, but not AK23 IgM, induced fragmentation of epidermal sheets. Together, these observations indicate that antibodies must gain access to Dsg3 integrated within desmosomes to induce the loss of keratinocyte cell-cell adhesion. These findings provide an important framework for improved understanding of B-cell tolerance and the pathophysiology of blister formation in pemphigus.